2020
DOI: 10.3390/su12072922
|View full text |Cite
|
Sign up to set email alerts
|

An Assessment of Age and Gender Characteristics of Mixed Traffic with Autonomous and Manual Vehicles: A Cellular Automata Approach

Abstract: Traffic congestion has become increasingly prevalent in many urban areas, and researchers are continuously looking into new ways to resolve this pertinent issue. Autonomous vehicles are one of the technologies expected to revolutionize transportation systems. To this very day, there are limited studies focused on the impact of autonomous vehicles in heterogeneous traffic flow in terms of different driving modes (manual and self-driving). Autonomous vehicles in the near future will be running parallel with manu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 47 publications
(46 reference statements)
1
7
0
Order By: Relevance
“…With regard to the risk factors related to the demographics of the drivers involved in traffic accidents, vehicle, and zone, the findings of the present study reported increased probabilities as regards the infractions of distracted young drivers (under 25 years old). These findings coincide with many conclusions of existing studies [ 69 , 70 , 71 ], which had reported similar observations on risky driving behaviors and violations of young drivers who are more susceptible to be involved in fatal crashes due to distraction activities (e.g., mobile phone use, radio, DVD, etc.). In this context, young drivers are inexperienced and easily distracted by interactions with music devices, texting and conversations on mobile phones resulting in slower reaction times [ 72 ].…”
Section: Discussionsupporting
confidence: 92%
“…With regard to the risk factors related to the demographics of the drivers involved in traffic accidents, vehicle, and zone, the findings of the present study reported increased probabilities as regards the infractions of distracted young drivers (under 25 years old). These findings coincide with many conclusions of existing studies [ 69 , 70 , 71 ], which had reported similar observations on risky driving behaviors and violations of young drivers who are more susceptible to be involved in fatal crashes due to distraction activities (e.g., mobile phone use, radio, DVD, etc.). In this context, young drivers are inexperienced and easily distracted by interactions with music devices, texting and conversations on mobile phones resulting in slower reaction times [ 72 ].…”
Section: Discussionsupporting
confidence: 92%
“…However, the authors expressed reservations, noting that events were often brief, with only half lasting two to three minutes. According to [30,31], further investigation is warranted to understand drivers' preferences in setting ACC or CACC parameters, considering factors like age, gender, and driving style in mixed traffic scenarios at road interchange facilities. In certain traffic scenarios, human drivers may choose to take control of the vehicle, either switching off the automation mode or activating it.…”
Section: Related Research Studiesmentioning
confidence: 99%
“…Accurately predicting traffic flow and grasping the dynamic change trend of traffic flow are key steps of ITSs, which are of great significance for alleviating traffic congestion, developing reliable traffic control and guidance strategies, and studying vehicle-road collaboration and autonomous driving [3][4][5][6]. Experience has shown that the monitoring and management of traffic states predicting in advance are often less effective than on-site deployment measures, and the benefits obtained by on-site deployment measures are more obvious [7,8]; therefore, traffic flow forecasting with big data technology has become the hottest research topic in the domain of traffic prediction [9,10].…”
Section: Introductionmentioning
confidence: 99%